Molecular phylogeny and taxonomy of the genus Nanocnide (Urticaceae) with particular attention to the Ryukyu Islands endemic N. lobata - Aoki, Satoshi; Li, Pan; Matsuo, Ayumi; Suyama, Yoshihisa; Ito, Motomi (Phytotaxa, 2023)
A plant named Nanocnide pilosa (Urticaceae) is assessed as a critically endangered species in Japan. However, this name has been placed in synonymy with N. lobata in the Flora of China, and this treatment is widely accepted outside of Japan. Although plants known as N. pilosa and N. lobata have been known to have morphological differences, their phylogenetic relationships have never been investigated using multiple samples per taxon. To elucidate the phylogeny and taxonomic status of N. pilosa and N. lobata, we conducted phylogenetic and population genetic analyses of the genus Nanocnide using internal transcribed spacer regions and MIG-seq together with morphological observations. Our results suggest that N. pilosa and N. lobata are sister taxa, and that each of them comprises a distinct clade in the MIG-seq tree. Based on these results, we propose treating N. pilosa and N. lobata as distinct species. Our study also revealed that N. pilosa has a widespread distribution in the subtropical regions of Mainland China and southern part of the Kyushu Island, Japan; whilst N. lobata is endemic to the Ryukyu Islands, Japan. In addition, we report new information on morphology of the remaining species of Nanocnide.